Role of Product Innovation and Brand Image Toward Customer Interest and Its Implication on Electronic Products Purchase Decision - Hendy Tannady; Herman Sjahruddin; Idris Saleh; Joseph M.J Renwarin; Arief Nuryana (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2022)
PT. TJA is one of the importer companies that has a variety of electronic products and is a supplier and distributor of cleaning service tools and various cleaning tools. This study aims to analyze the effect of product innovation and brand image on customer interest which has an impact on purchase decisions for PT TJA's products. Sources of data used for research are secondary data and primary data. The research data was obtained by distributing questionnaires to respondents and through literature review. The independent variables are product innovation and brand image, the mediating variable is customer interest and the dependent variable is purchase decisions. The method of analysis in this study uses linear regression analysis with SPSS 22. Total respondents in this study is 140 folks, all respondents had made purchases and used products which were sold by PT TJA. The results of this study indicates that all variables have an effect on purchase decision.